Second-Order Lagrange Multiplier Rules in Multiobjective Optimal Control of Infinite Dimensional Systems Under State Constraints and Mixed Pointwise Constraints - Nguyen Dinh, Tuan (Applied mathematics & optimization, 2021)
We investigate a multiobjective optimal control problem, governed by a strongly continuous semigroup operator in an infinite dimensional separable Banach space, and with final-state constraints, pointwise pure state constraints and a mixed pointwise control-state constraint. Basing on necessary optimality conditions obtained for an abstract multiobjective optimization framework, we establish a second-order Lagrange multiplier rule, of Fritz-John type, for local weak Pareto solutions of the problem under study. As a consequence of the main result, we also derive a multiplier rule for a multiobjective optimal control model driven by a bilinear system being affine-linear in the control, and with an objective function of continuous quadratic form.